Analysis of the Promotion Mix Strategy on the Number of Martabe Savings Customers at PT Bank Sumut, Tembung Branch Office - Immanuel Edy Suranta Sebayang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The subject of this research is